Does substance matter? A model of qualitative portfolio allocation and application to German state governments between 1990 and 2010. (May 2015) - Raabe, Johannes; Linhart, Eric
Gamson's Law of office distribution tells us approximately how many ministries each member of a coalition will receive. However, the question of which ministries are allocated to which parties according to a more general party motivation remains largely open. In a model-theoretic investigation of portfolio allocation we focus on the characteristics of the distributional process concerning the qualitative differences of ministries: which motivation drives parties to choose or disregard certain ministries? Applying the technical framework of divisor methods for our model and estimating party preferences according to their election manifestos, we find that substance indeed does matter. Parties seek to obtain ministries in those policy fields which they mention more intensively in their electoral manifestos and at the same time spread their ministerial control broadly. Furthermore, we find that bigger parties are not qualitatively repaid for their usually observable quantitative loss.